Primula yanbianensis (Primulaceae), a new species in Primula sect. Cortusoides from Sichuan, China - Tian Shuai; Hong-qiang Lin; Lei Cai; Yu-fan Chen; Zhi-kun Wu (PhytoKeys)
Primula yanbianensis T.Shuai, Lei Cai & Z.K.Wu, a new species of Primulaceae from Sichuan, China, is described and illustrated. Morphological evidence supports P. yanbianensis as a member of P. sect. Cortusoides, which is characterised by lack of farina, generally well furnished with multicellular hairs, subrounded leaf blades are more or less lobed, with distinct petiole and a deeply cordate base and campanulate or narrowly campanulate calyx not accrescent after anthesis. The new species is characterised by having umbel in whorls of 1–2, scape usually lower than leaf clusters, bracts broadly ovate and rose to pink petals distinctly veined. The distribution, morphological comparison with closely-related species and conservation status of the new species are also provided.